Integration of GIS and AHP for sanitary landfill site suitability analysis: A case study of Batangas province - Canlas, Alen Clyde A. (Animo Repository, 2021)
Finding a suitable site for sanitary landfilling has become a major challenge for many local government units (LGU) and private entities amidst the shortage of sanitary landfills (SLF) as means of solid waste disposal. In siting for a suitable SLF area, the different site selection parameters specified under the law must be taken into consideration and serve as the basis of the suitability of the SLF site. Among these parameters, 10 were identified for the SLF site suitability analysis of this study which includes proximity to known sites of groundwater resources, surface waters, faults, built-up areas, protected areas, and airports, and the geo-environmental characteristics corresponding to the local geological conditions, soil properties, topography, and the vulnerability to rain-induced landslide and flooding hazards. This study demonstrates a scientific approach to identifying and mapping suitable SLF areas through the integration of Geographic Information System (GIS) and Analytic Hierarchy Process (AHP) to the case of Batangas province. Weighted linear combination (WLC) was used as the preferred geoprocessing tool in the evaluation of the SLF site suitability. This study identified and mapped an area of 884.42 ha. as highly suitable for sanitary landfilling, 62,486.15 ha. as moderately suitable, and 248.89 ha. as marginally suitable, with the remaining areas of the study area being unsuitable for sanitary landfilling. The municipality of San Juan was identified as having the most suitable areas while the municipalities of Balete, Mataas na Kahoy, and San Nicolas have no suitable areas for sanitary landfilling, reducing the likelihood of having an SLF in each LGU. Of the 7 operating SLFs in the province, 5 were identified to be within unsuitable areas while 1 SLF was partially within an unsuitable area. This study identified and mapped the suitable sanitary landfilling areas which can be used to support future solid waste management policies and decisions of the different stakeholders in a manner that considers the negative impacts of SLFs on humans and the environment and reflects compliance with the provisions of the law.